Dispute management in Islamic financial institutions: a case study of near sukuk defaults - Oseni, Umar Aimhanosi (Emerald Group Publishing, 2014)
Purpose – The purpose of this paper is to examine the vital importance of dispute management in cases of both near and outright sukuk defaults. With the case studies, this study examines the vital importance of dispute management in cases of both near and outright sukuk defaults. With a number of case studies, the study shows how debt restructuring can play a significant role as a dispute management procedure recognized in Islamic law.